Effect of the concentration of uronic acids in Opuntia mucilage on the removal of heavy metals and water quality of the Yautepec River, Mexico - Edgar González-Avilez; Francisco Rodríguez-González; Silvia Viridiana Vargas-Solano; Alex Osorio-Ruiz; M.P. Jonathan; Lorena Elizabeth Campos-Villegas (Arabian Journal of Chemistry, 2024)
The purpose of this study was to analyze the effect of uronic acid (UA) content of Opuntia Ficus-indica (OFI) mucilages on the removal process of heavy metals (HM) present in water samples (WS) from the Yautepec River, Mexico. For this, mucilages from nopals with different maturation ages were extracted (20–35, 80–100 and 550–600 days, namely, M1, M2 and M3, respectively); and the UA content was determined by UV–vis spectrophotometry. Furthermore, ten WS were collected in different fluvial sites of the river; and the pH, electrical conductivity (EC) and turbidity were determined in situ; and the concentration of HM (cooper, cadmium, chromium, nickel, lead, zinc, iron, manganese, and arsenic) was quantified by atomic absorption spectrometry. Subsequently, the WS were used to evaluate the effect of UA content of M1, M2, and M3 on the removal of HM by the jar method; then, the pH, EC, turbidity, and total percentage concentration of HM removed (%TCHR) were determined. Also, the functional groups of OFI mucilages were identified by Fourier transform infrared spectroscopy (FTIR) before and after the HM removal process. The results show that the UA content increased with the maturation age of the nopals, and M3 exhibited the highest content with 2.22 mg/mL; the WS showed a high content of iron, manganese, and lead with 1546, 209 and 80.8 μg/L, respectively. After the HM removal process, the %TCHR was determined, and it was found that M3 achieved the highest percentage with 90.3 %. The concentration of UA in the mucilage was a factor that influenced in the removal of HM, as well as the initial pH conditions and the initial concentration of HM. Finally, the spectra of FTIR showed typical bands of pectic polysaccharides such as carboxyl, carbonyl, and hydroxyl, which interacted with HM by electrostatic interactions.